The feasibility of introducing capital gains tax in Malaysia - Hingun, Mohsin (s.n, 2012)
In the modern world, taxation remains a major source of revenue to governments which enables them to carry out the legitimate function of discharging financial obligations toward their citizen. Government resource are various. As the return for the privilege of membership of an organized society, every citizen is required to contribute fairly in the form of tax payment. From immemorial times, the contribution from taxes for the well functioning of government has been acknowledged. Currently the Malaysia Government derives its revenues principally from a number of sources but capital gains tax is restricted to gains accruing from the transfer of real property or shares in a real property company